The impact of health education on quality of life of patients with hypertension - Michoń, Julitta; Uchmanowicz, Izabella; Lomper, Katarzyna; Rycombel, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction: Hypertension as any chronic disease  affects the functioning of a patient in the bio-psycho-social dimension. Impairs functioning in everyday life and becomes a reason for the resignation of the previous habits. These changes may contribute to depressed mood, leading to depression. Therefore, a key role in the treatment of the hypertension is attributed to health education, which is designed to help the patient find a new habits and to function in spite of the limitations of the disease. Aim: To examine the impact of health education on the quality of life of patients with hypertension. To examine sociodemographic factors: age, sex, education, place of residence, professional activity on the quality of life of patients with hypertension . Material and methods: The study was conducted among 100 patients (40 women and 60 men) diagnosed with hypertension. The study used a survey of the questionnaire developed by authors of this study consisting of 12 questions and a questionnaire to assess the overall quality of life SF-36 (Short Form-36). Results: Analyzing the individual elements of the study it can be concluded that health education had a positive impact on lifestyle modification taking into account all the issues discussed . Analysis of the quality of life measured by the SF -36 in patients who were educated QoL showed higher scores compared to patients before health education in domains: PF ( 75.8 vs. 78.0, p = 0.544, ns) , RP (64.9 vs. 68.0, p = 0.616 , ns) , BP (83.4 vs. 87.9, p = 0.119, ns) , VT (64.0 vs. 71.2, p < 0.001) , SF (80.6 vs. 84.2, p = 0.239, ns) , MH (62.8 vs. 72.0, p < 0.001) and in the domain RE (71.0 vs. 73.3, p = 0,697 ns) . Lower quality of life assessment after health education was observed in one domain questionnaire. This result was as follows: GH (48.5 vs. 47.5, p = 0.393, ns) Conclusions: Health education improves the quality of life of patients with hypertension. The quality of life is affected by age, gender, education and place of residence . Poorer quality of life was observed in patients over 60 years of age. Women are characterized by poor quality of life in all  dimensions of SF-36 quetionnaire. The higher  level of education has a positive effect on the quality of life . Persons living in cities are characterized by a higher quality of life assessment.